Single-molecule conductance studies of organometallic complexes bearing 3-thienyl contacting groups - Bock,S; Al-Owaedi,OA; Eaves,SG; Milan,DC; Lemmer,M; Skelton,BW; Osorio,HM; Nichols,RJ; Higgins,SJ; Cea,P; Long,NJ; Albrecht,T; et al. (Chemistry - A European Journal, 2017)
The compounds and complexes 1,4-C6H4(C≡C-cyclo-3-C4H3S)2 (2), trans-[Pt(C≡C-cyclo-3-C4H3S)2(PEt3)2] (3), trans-[Ru(C≡C-cyclo-3-C4H3S)2(dppe)2] (4; dppe=1,2-bis(diphenylphosphino)ethane) and trans-[Ru(C≡C-cyclo-3-C4H3S)2{P(OEt)3}4] (5) featuring the 3-thienyl moiety as a surface contacting group for gold electrodes have been prepared, crystallographically characterised in the case of 3–5 and studied in metal|molecule|metal junctions by using both scanning tunnelling microscope break-junction (STM-BJ) and STM-I(s) methods (measuring the tunnelling current (I) as a function of distance (s)). The compounds exhibit similar conductance profiles, with a low conductance feature being more readily identified by STM-I(s) methods, and a higher feature by the STM-BJ method. The lower conductance feature was further characterised by analysis using an unsupervised, automated multi-parameter vector classification (MPVC) of the conductance traces. The combination of similarly structured HOMOs and non-resonant tunnelling mechanism accounts for the remarkably similar conductance values across the chemically distinct members of the family 2–5.